Purinergic signaling in schistosomal infection - Claudia Lucia Martins Silva (Biomedical Journal, 2016)
Human schistosomiasis is a chronic inflammatory disease caused by blood fluke worms belonging to the genus Schistosoma. Health metrics indicate that the disease is related to an elevated number of years lost-to-disability and years lost-to-life. Schistosomiasis is an intravascular disease that is related to a Th1 and Th2 immune response polarization, and the degree of polarization affects the outcome of the disease. The purinergic system is composed of adenosine and nucleotides acting as key messenger molecules. Moreover, nucleotide-transforming enzymes and cell-surface purinergic receptors are obligatory partners of this purinergic signaling. In mammalian cells, purinergic signaling modulates innate immune responses and inflammation among other functions; conversely purinergic signaling may also be modulated by inflammatory mediators. Moreover, schistosomes also express some enzymes of the purinergic system, and it is possible that worms modulate host purinergic signaling. Current data obtained in murine models of schistosomiasis support the notion that the host purinergic system is altered by the disease. The dysfunction of adenosine receptors, metabotropic P2Y and ionotropic P2X7 receptors, and NTPDases likely contributes to disease morbidity. Keywords: Purinergic receptor, NTPDases, Schistosomiasis, Macrophages, Endothelial cell, Inflammation